Detection of the fungicides thiophanate menthyl, benomyl and triadimephon in extracts of rubber tree through thin layer chromathography and bioautography - Barrueto Cid, Luis Pedro (Pesquisa Agropecuaria Brasileira, 2014)
Translocation of the fungicides thiophanate metyl, benomyl and triadimephon was followed by thin layer chromatography and bioautography in nursery plants of Hevea brasiliensis in stage of apical budding burst: It was found out that any of the three fungicides may be detected in the new emerging leaves at 7, 14 and 21 days old after the spray application on the botton flush leaves. Triadimephon was not detected on the seventh day after spray application; while thiophanate methyl was detected on the seventh and fourteenth days. Benomyl was detected on the seventh, fourteenth and twenty-first days after the spray application. Both, triophanate methyl and benomyl were detected on the last botton flush leaves but not on the young leaves, as was expected. It is suggested that this persistence effect may be important in controlling the South American leaf blight in the rubber tree.